High-Output Heart Failure Contributing to Recurrent Epistaxis Kiesselbach Area Syndrome in a Patient With Hereditary Hemorrhagic Telangiectasia - Venugopal Brijmohan Bhattad MD; Jennifer N. Bowman BA; Hemang B. Panchal MD, MPH; Timir K. Paul MD, PhD (SAGE Publishing, 2017)
Hereditary hemorrhagic telangiectasia (HHT), also known as Osler-Weber-Rendu syndrome, is a rare genetic blood disorder that leads to abnormal bleeding due to absent capillaries and multiple abnormal blood vessels known as arteriovenous malformations. A feature of HHT is high-output heart failure due to multiple arteriovenous malformations. High-output heart failure can lead to recurrent epistaxis Kiesselbach area syndrome (REKAS), further exacerbating heart failure through increased blood loss and resultant anemia. We report a patient with HHT who presented with high-output heart failure contributing to REKAS. In patients with REKAS, we propose if anemia is present, REKAS can be avoided by correcting the anemia by increasing the hemoglobin level to greater than 9 to 10 g/dL. This decreases hyperdynamic circulation and reduces pressure in the blood vessels of the nose.